A Normative Behavior of Pre-Travel Health Consultation and the Associated Factors among Travelers - I Gede Nova Ariawan; Kadek Eka Swedarma; Ni Putu Emy Darma Yanti (Jurnal Ners, 2021)
Introduction: Travelers may transmit diseases due to their behavior of travel, consequently travelers should consider preventive measurement through pre-travel health consultation seeking behavior. Pre-travel health consultation is a particular preparation ideally conducted by international travelers to obtain risk assessment and management to prevent the transmission of diseases. This study investigates the relationship of socio-demographic characteristics and itinerary on pre-travel health consultation behavior among international travelers in Badung, Bali.Methods: A descriptive-correlative design using a cross-sectional approach employed 125 participants determined by a purposive sampling technique performed in the ten tourist destinations of Badung Regency. Data collection was conducted on February 15th until March 5th, 2020. Data demography, travel plan, and anonymous questionnaires regarding pre-travel health consultation behavior are used in this research. The Gamma coefficient correlation and Kruskal-Wallis statistic tests were performed in the study for bivariate analysis.Results: The results showed that age (p<0.0001; r=-0.650) and past-travel history to Bali (p=0.004; r=-0.475) were significantly correlated with pre-travel health consultation behavior among international travelers in Badung, Bali. Meanwhile sex, nationality, last education, travel duration, and types of the destination visited were not significantly associated with pre-travel health consultation behavior among international travelers in Badung, Bali (p>0.05).Conclusion: The age and past-travel history to Bali seem to be predictors for travelers to uptake pre-travel health consultation, thus nurses should be able to promote the implementation of pre-travel health consultation by utilizing the media promotion appropriately adjusted to the age of travelers and travel experience.